2022
DOI: 10.7759/cureus.31015
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Screen Time and Dry Eye Symptoms During the COVID-19 Pandemic in the Pediatric Population of the Western Region of Saudi Arabia

Abstract: To measure the prevalence of dry eye disease (DED) and study the relationship between screen time and dry eye symptoms in the pediatric population during the coronavirus disease 2019 (COVID-19) pandemic using the Ocular Surface Disease Index (OSDI) questionnaire. MethodsIn this descriptive, observational, cross-sectional study, our survey included the pediatric population, ages 1 to 18 years, of both genders, who attended outpatient clinics of two main hospitals in Jeddah, Saudi Arabia. Collected data included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…The results of the study showed that 76.1% of participants had symptomatic DED, while 23.9% had no DED. The authors found an increase in the symptoms of DED during the COVID-19 pandemic due to prolonged screen time exposure [ 8 ]. Another study conducted in 2022 by Garca-Ayuso et al aimed to assess the prevalence of DED using the OSDI questionnaire among university students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the study showed that 76.1% of participants had symptomatic DED, while 23.9% had no DED. The authors found an increase in the symptoms of DED during the COVID-19 pandemic due to prolonged screen time exposure [ 8 ]. Another study conducted in 2022 by Garca-Ayuso et al aimed to assess the prevalence of DED using the OSDI questionnaire among university students.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies published to investigate the prevalence of DED during the COVID-19 pandemic and the effect of e-learning on the development of DED In 2022, Wejdan Alnahdi et al conducted a study to measure the prevalence of DED and its association with screen time in the pediatric population during the COVID-19 pandemic using the Ocular Surface Disease Index (OSDI) questionnaire. The results of the study showed an increase in the symptoms of DED during the COVID-19 pandemic due to prolonged screen time [ 8 ]. Another study conducted by Santa-Cruz-Pavlovich et al in 2023 aimed to assess the difference in the incidence of DED since the onset of online courses started using OSDI.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 , 6 ] Second, the use of electronic devices for education and entertainment prolonged screen time in young people potentially leading to adverse implications on ocular surface health. [ 7 ] A prospective study by Krolo et al . [ 8 ] found that face mask wear also exacerbated dry eye symptoms in VDT users.…”
mentioning
confidence: 99%